SELF-DIRECTED Learning Aptitude and Engagement of Students on Virtual REALITY TECHNOLOGY in A UNIVERSITY IN Jiangxi Province, China - Teng, Fengyu (International Journal of Social Sciences and Public Administration, 2024)
This study aims to explore the relationship between Nanchang Institute of Technology students’ self-directed learning ability and virtual reality technology participation. Research results show that students’ self-directed learning abilities (including self-management, motivation, and self-monitoring) are significantly related to behavioral, cognitive, and emotional engagement with virtual reality technology. The age factor has a significant impact on students’ self-directed learning ability evaluation, while the gender and grade factors have no significant impact. The self-directed learning approach in virtual reality technology enhances student engagement and provides a more autonomous and immersive learning experience. The study recommends that educators and designers incorporate elements that promote self-management, motivation, and self-monitoring into VR learning environments to improve overall student engagement and learning outcomes.